Dynamic Coupling at the Ångström Scale. (7th December 2015) - Dey, Krishna Kanti; Pong, Frances Ying; Breffke, Jens; Pavlick, Ryan; Hatzakis, Emmanuel; Pacheco, Carlos; Sen, Ayusman
Abstract: While momentum transfer from active particles to their immediate surroundings has been studied for both synthetic and biological micron‐scale systems, a similar phenomenon was presumed unlikely to exist at smaller length scales due to the dominance of viscosity in the ultralow Reynolds number regime. Using diffusion NMR spectroscopy, we studied the motion of two passive tracers—tetramethylsilane and benzene—dissolved in an organic solution of active Grubbs catalyst. Significant enhancements in diffusion were observed for both the tracers and the catalyst as a function of reaction rate. A similar behavior was also observed for the enzyme urease in aqueous solution. Surprisingly, momentum transfer at the molecular scale closely resembles that reported for microscale systems and appears to be independent of swimming mechanism. Our work provides new insight into the role of active particles on advection and mixing at the Ångström scale.